Influence of Arbuscular Mycorrhiza and Phosphorus Levels on Dry Matter Production and Nutrients Uptake by Tomato Seedlings (Progressive Agriculture, 2013)
To investigate the effects of arbuscular mycorrhiza (AM) and phosphorus (P) rates on the uptake of primary and secondary nutrients by tomato (Lycopersicon esculentum Milli) cv. BARI Tomato-2 seedlings, under P levels ranging from low to excessive, plants were grown in five levels of P (0, 7.5, 15.0, 22.5 and 30.0 mg P kg-1 soil) as TSP, either inoculated with AM or without AM. The total dry matter yield and uptake of N, P, K, S, Ca and Mg nutrients was significantly influenced by AM inoculation. Nutrient use efficiency in the AM-inoculated seedlings was also significantly higher than that in uninoculated seedlings. The application of different levels of P lonely increased different nutrients and its uptake positively up to certain level, but at higher level influenced negatively. The N, P, K, S, Ca and Mg content and uptake all were the highest when P applied @ 30 kg ha-1 and the lowest @ 0 kg P ha-1 but uptake found the lowest @ 60 kg P ha-1. There was a significant interaction effect of AM and P levels on nutrients content and their uptakes positively up to certain level, but at higher level of P combination influenced negatively. Among the treatment combinations, P30 x I showed the highest nutrient contents under study and their uptakes but dry matter yield gave the highest value when AM was applied with P @ 15 kg ha-1.DOI: http://dx.doi.org/10.3329/pa.v19i2.16932 Progress. Agric. 19(2): 75 - 84, 2008